Structure Analysis and Optimization for Main Drive Gearboxes of the CDQ Elevator Based on FEA - Xu Jianzhong; Kang Shaobo; Xu Junwei; Shao Guangjun; Ruan Wenhao (Jixie chuandong)
The main drive gearbox of the coke dry quenching (CDQ) elevator in a steel plant has experienced serious failure after serving a period of time in service. The process of maintenance shows that the pinion shaft and the bearing of the final stage are most severely damaged. For further research of damage causes, this study will calculate the capacity and life of the bearing by KISSsoft software, and meanwhile build a 3D model of the CDQ elevator gearbox for the finite element analysis (FEA) by using software Inventor Nastran. As a result, the weakness of the structure about the gearbox is identified and the optimization is implemented contrapuntally. According to the comparison before and after maintenance, the improvement effect is obvious.